Structures of Morality and Allegiance in the Character Arc Story. (5th March 2022) - Kelly, Rory; Cumming, Samuel
Abstract: The view that allegiance to characters is a matter of general moral assessment, as developed by Carroll (1984) and Smith (1995), has the resources to respond to counter-examples proposed in the literature, including appeals to anti-heroes, rough heroes and other 'reprehensible characters' that garner our allegiance. It can even admit non-moral factors as subterranean influences on moral assessment. Nevertheless, the view requires that the characters we most favour are those with the highest moral standing, and this does not seem to be true of the character arc story (Kelly, 2020 ). Rather, the mixture of good and bad impulses in the protagonist is set off by the unalloyed moral example of the moral centre, a supporting character whose fate may barely interest us. We conclude that narrative theory is better served by allowing the moral hierarchy of a story to differ from the rank order of its allegiances, and hence that audience affiliation is not simply a matter of moral assessment.